Erythropoietic factor and Plasma Volume in Chronic Hypoxia Height - Pérez Enciso, Juan Julio (1966)
This work has been initiated by the incessant concern about the research of erythropoietin, which corresponds to one of the large and important chapters of Hematology. This research work is developed in the Institute of Andean Biology, Faculty of Medicine, San Fernando, with a central laboratory in Lima, and another in the mining town of Morococha, to 4.540 meters above sea level, located in the Central Sierra of Peru. With the extensive facilities provided by the Institute, it has been possible to carry out this work, for which a group of six students of Medicine of the National University of San Marcos moved to that place for the collection of the work material. Thinking about the complicated mechanism of a plasma humoral factor, which since 1906 has been termed by Carnot and Deflandre, as haemopoietin; Grant later and Root (1) made ​​a review regarding the fundamental stimulus of erythropoiesis at that erythropoietic stimulating substance Jalavisto Bonsdorlf and (2) have referred to as erythropoietin. In 1950 Reissmann (3) did parabióticas experiences in rats demonstrating erythropoietic stimulating factor, then place them in a hypoxic atmosphere.